Evaluasi Dan Perencanaan Sistem Drainase Berwawasan Lingkungan Pada Kecamatan Simpang Empat - Muhammad Nur Ramadhan; Chairul Abdi; Mahmud; Gusti Ihda Mazaya (Prodi Teknik Lingkungan Fakultas Teknik Universitas Lambung Mangkurat, 2026)
Inundation can occur because the capacity of natural or artificial channels can no longer accommodate the flow of incoming rainwater. According to the 2015 Tanah Bumbu Regency Drainage Masterplan Review, almost all of the places that become puddles in Simpang Empat District are in residential areas, with a length of time of one inundation or until the rain stops with a height of ± 20 cm. The purpose of this plan is to analyze the planned flood discharge, evaluate the capacity of the drainage channel, recommend new channel dimensions, recommend infiltration well dimensions and create a new dimension layout in the planning catchment area. The analysis carried out in this plan is hydrological and hydraulics analysis with maximum daily rainfall data for 10 years (2012-2021). From the results of the calculation of the planned flood discharge it can be concluded that the minimum discharge is 0.06 m3/s in segment 14, while the maximum discharge is 0.20 m3/s in segment 12. This planning uses the Storm Water Management Model (SWMM) software, with using SWMM, the conditions that occur in the field can be modeled by incorporating the parameters recorded in the actual conditions. Improvement of the drainage channel by re-planning the dimensions of the channel, is recommended for segment 14 which is 0.52 m wide, 0.62 m high while for segment 12 which is 0.81 m wide and 0.86 m high. Keywords: Evaluation, Flood Discharge, Inundation, SWMM